Extraction of Fibre from Young Bamboo for Application in Textile Production - Cholthicha Sarikanon; Thanate Piromgarn; Songwut Egwutvongsa (Tekstilec, 2024)
Natural bamboo fibres have the potential for use in the production of eco-friendly and sustainable textile materials, and have numerous advantages over synthetic fibres. As such, the main aim of this study was to assess the benefits of using raw materials in textile production, including a reduction in energy consumed and time spent, and the reduced use of chemicals that impact the environment, suggesting a sustainable alternative to conventional materials. Thus, natural bamboo fibres exemplify a raw material that can be used in textile applications in various sectors. To investigate the chemical and mechanical separation of young 30–120-day-old bamboo fibres for the purpose of bamboo fibre extraction, experiments were conducted in which the concentration of caustic soda (NaOH) used to separate the fibres was reduced to 5 g/l at 100 °C for 90 minutes, demonstrating that natural 60-day-old bamboo fibres can be separated effectively into single fibre. Furthermore, when natural bamboo fibres are combined with recycled polyester (r-PET) at a blend ratio of 30% to 70% (% by weight), respectively, the fabric’s unique textural characteristics during weaving make it suitable not only for the fabrication of various textile products, but also for a wide range of additional applications.